Postoperative pain and wound complications in pediatric transverse laparotomy: mass closure versus layered closure-a randomized clinical trial - Ituen, Monday A.; Akpanudo, Emem I.; Eyo, Catherine S.; Ekot, Ekerete A. (International Journal of Contemporary Pediatrics, 2025)
Background: Optimal abdominal wall closure technique in pediatric laparotomy remains debated. This study compared wound complications and postoperative analgesia requirements following mass versus layered closure in children undergoing transverse laparotomy. Methods: This single-center randomized clinical trial was conducted at the university of Uyo teaching hospital, (UUTH) Nigeria, between 2021 and 2023. Children aged ≤5 years who underwent laparotomy via a transverse abdominal incision were eligible. Excluded were previous laparotomy, abdominal wall defects, or contaminated or dirty wounds. Participants were randomly assigned to either mass or layered closure. In both groups, closure was performed using polyglactin 910 (Vicryl™) sutures by senior surgical trainees under standardized operative and postoperative protocols. Primary outcomes included surgical site infection (SSI), wound dehiscence, incisional hernia, and duration of postoperative analgesia. Follow-up lasted one year. Chi-square, Fisher’s exact, and Wilcoxon rank-sum tests were used to compare outcomes between groups, with significance set at p<0.05. Results: A total of 111 children were enrolled (56 mass closure; 55 layered closure). SSI was the most common complication, occurring in 11 patients (9.9%), followed by incisional hernia in 4 (3.6%) and wound dehiscence in 2 (1.8%). Wound dehiscence occurred only in the layered group (n=2, 3.6%), while incisional hernias occurred equally in both groups (n=2 each; 3.6%). Clean-contaminated wounds were significantly associated with SSI (p=0.024), but there were no statistically significant differences in complication rates or analgesia requirements between groups. Conclusions: Both closure methods appear equally safe in paediatric transverse laparotomy when standard surgical technique is followed. Routine follow-up for at least one year is recommended to detect late complications.